Petrology and geochronology of felsic volcanics in the Sabga area (Bamenda Highlands): implications for age variation along the Cameroon Volcanic Line - Bate Tibang,E.E.; Suh,C.E.; Cottle,J.; Ateh,K.I.; Tiabou,A.F.; Nche,L.A.; Che,V.B.; Vishiti,A. (Journal of Geosciences, 2017)
The textural characteristics of felsic lavas and ignimbrites in the Sabga area along the continental segment of the Cameroon Volcanic Line (CVL) are documented in this study. Two rhyolitic lava flows separated by mafic and rhyodacitic lava flows were dated by zircon LA-ICP-MS technique in order to constrain the timescales of successive flow emplacement as well as magma chamber processes in this volcanic field. The studied samples have rheomorphic characteristics such as eutaxitic textures defined by elongated fiamme as well as deformed and welded glass shards. They exhibit flow banding and contain spherulitic groundmass. Rhyolitic autobreccias and ignimbrites are widespread in the Sabga area, are peralkaline in nature and their ages are broadly similar at ˜23.0 ± 0.3 Ma (23.34 ± 0.34 Ma for the ignimbrite and 22.98 ± 0.28 Ma for the rhyolitic autobreccia unit). These ages suggest rapid recharge of magma into a periodically replenished and open chamber. The felsic rocks in the Sabga area and around the Bamenda Highlands are also younger compared to other felsic units along the CVL (29 Ma to 69.4 ± 0.4 Ma).
Keywords: Cameroon Volcanic Line; Bamenda Highlands; zircon dating; flow banding; rhyolitic ignimbrite; rhyolitic autobreccia